2011
DOI: 10.1007/s11282-011-0069-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of non-syndromic supernumerary teeth in a cohort of Turkish patients

Abstract: Objectives To investigate the frequency, prevalence, distribution, sex differences and characteristics of supernumerary teeth in a referred non-syndromic Turkish population. Methods A total of 5200 panoramic radiographs of patients who presented at the Department of Oral and Maxillofacial Radiology from July 2008 to August 2010 were evaluated. Demographic variables (age and sex), location, morphology, classification, number of supernumerary teeth, distribution, side and eruption status of supernumerary teeth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 19 publications
(88 reference statements)
1
25
0
Order By: Relevance
“…Mostly conical supernumerary teeth were observed in the studies [33]. More tubercular and fewer supplemental forms were observed to follow conical forms.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Mostly conical supernumerary teeth were observed in the studies [33]. More tubercular and fewer supplemental forms were observed to follow conical forms.…”
Section: Discussionmentioning
confidence: 81%
“…The studies on supernumerary teeth in Turkish population report a prevalence frequency of 0.75-2.3% [20,[30][31][32][33][34][35][36][37]. In a great majority of the studies, more supernumerary teeth have been observed in men than in women (1.28/-1.91/1) [20,30,31,32,33,34].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations